PENGARUH STRATEGI GUIDED NOTE TAKING BERBANTU MEDIA VIDIO TERHADAP HASIL BELAJAR SISWA PADA MATERI TEMATIK KELAS IV SDN 5 RAMBANG - Hevi Hevi Triday Yanti; Amir Hamzah; Faisal; Ahmad Syarifuddin; Ayu Nurshawmi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to determine the effect of the Guided Note Taking strategy with the aid of video media on student learning outcomes in grade IV SDN 5 Rambang subjects. The method used in this research is a quasi-experimental method in the form of One Group Fretest-posttest with a total sample of 44 students. The analytical technique used in this study is the normality test, homogeneity test, and t test using the SPSS 22 for windows software program. the posttest mean is 90.00 and the standard deviation is 6.43. Meanwhile, for the control class, the average fretest score was 67.6 and the standard deviation was 7.49, the posttest average was 83.5 and the standard deviation was 5.69. video has a significant effect on the learning outcomes of fourth grade students at SDN 5 Rambang.